Future Policy Planning of Law Enforcement and Criminal Execution to Face Covid-19 Pandemic - Rosdayana Khairuummah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
The Covid-19 pandemic is first reported in late December 2019 in Wuhan, Hubei Province of China, Covid- 19 has rapidly spread worldwide. In the middle of 2019, by paying attention to the victims affected by covid-19 in the country more and more, the government, through Presidential Decree No. 11 of 2020 on The Determination of Public Health Emergency Corona Virus Disease 2019 (Covid-19), has established a public health emergency, following the event as a non-natural national disaster through the Presidential Decree No. 12 of 2020 on the Determination of Non-natural Disasters The Spread of Corona Virus Disease 2019 (Covid-19) as a national disaster, attempts to prevent the transmission of the Covid-19 virus are also carried out by the government through the Correctional Institution and Detention Center and Child Development Institutions as a closed institution that in actually experienced overcrowding conditions that facilitate the transmission of Covid-19. In the face of overcrowding prison, the Ministry of Law and Human Rights, the Directorate General of Corrections, has implemented several policies on the Correctional Institutions, Detention Center and Child Development Institutions. Considering the number of people affected by the Covid-19 pandemic is increased, it is not yet known exactly when it will decrease in the graph, criminal acts will continue to occur so that it will cause problems for the execution of unlawful deprivation of liberty that will have implications for the enforcement of criminal law in the future.